(untitled) (Medical Forum Monthly, 2024)
Objective: To document the effect of back care advice on the frequency and severity of low backache in pregnancy. Study Design: Comparative cross sectional study Place and duration of Study: This study was conducted in Antenatal Outpatient department of Obstetrics & Gynecology, Khyber Teaching Hospital, Peshawar from Jan 2012 to Jun 2012. Materials and Methods: Advice on back care was made available to a group of primigravidae women as early in their pregnancy as possible. For comparison another group of primigravidae women for which no such advice was given was recruited. Both groups were followed throughout pregnancy for the occurrence of low back pain and its severity. Results: The study comprised of 200 primigravidae with 100 women each in study group and control group. Seventy eight women in study group and 65 in the control group reached term. Among the study group 28.2 % experienced low backache in contrast to control group in which 56.9% developed back pain during pregnancy. In the study group 68.1% were having mild, 27.2 % moderate and only 4.5% severe pain. In the control group majority of women experienced moderate to severe pain. Furthermore the study group had pain much later in gestation as compared to control group. Conclusion: Low backache was less common inprimigravidae women who receive advice on back care early in pregnancy. Low back pain, if present was less troublesome and severe than pregnant women for whom no such advice was available.